Dropping plates to pick up aliens: towards a standardised approach for monitoring alien fouling species. Issue 4 (2nd October 2021) - Loureiro, TG; Peters, K; Robinson, TB
Abstract : Biological invasions pose a major threat to biodiversity and significant investment is required to prevent the introduction of alien species, contain introduced populations and mitigate associated impacts. The implementation of standardised long-term monitoring programmes enables the early identification of new alien species, the tracking of spread, the assessment of the effectiveness of management interventions, and an understanding of temporal and spatial trends. Globally, fouling species are known to cause economic losses through accumulation on vessel hulls and port infrastructure and via the disruption of aquaculture activities. Additionally, fouling taxa can have ecological impacts in recipient systems, most often driven by their dominance in biological interactions. In South Africa, this group accounts for the majority of marine alien taxa. Accordingly, this study tested an approach for monitoring fouling biota using open and caged PVC settlement plates deployed in marinas. After 16 weeks, plates were removed, biota identified, and relative abundance captured as percentage cover. This method proved to be effective, logistically simple and cost-efficient. Twenty-four taxa were recorded, of which 58% were invasive species. It is recommended that this monitoring approach be implemented around the South African coast as a first step to providing key information to inform management and research.